2010
DOI: 10.1371/journal.pone.0010393
|View full text |Cite
|
Sign up to set email alerts
|

Dual Function of a Bee Venom Serine Protease: Prophenoloxidase-Activating Factor in Arthropods and Fibrin(ogen)olytic Enzyme in Mammals

Abstract: Bee venom contains a variety of peptides and enzymes, including serine proteases. While the presence of serine proteases in bee venom has been demonstrated, the role of these proteins in bee venom has not been elucidated. Furthermore, there is currently no information available regarding the melanization response or the fibrin(ogen)olytic activity of bee venom serine protease, and the molecular mechanism of its action remains unknown. Here we show that bee venom serine protease (Bi-VSP) is a multifunctional en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 54 publications
3
68
0
Order By: Relevance
“…The findings that Bi-VSP activates prothrombin and that Bi-VSP also acts as a fibrin(ogen)olytic protease [13] suggest that Bi-VSP is used to facilitate the spread of bee venom throughout the bloodstream, as has been demonstrated for snake venom fibrin(ogen)olytic enzymes, which remove fibrinogen effectively and, thereby, reduce blood viscosity [23], [24]. Given the similarity in plasmin targeting with textilinin-1, an anti-bleeding agent [7][9], Bi-KTI is likely to be an antifibrinolytic agent that reduces bleeding at the sting site of victims.…”
Section: Resultsmentioning
confidence: 96%
“…The findings that Bi-VSP activates prothrombin and that Bi-VSP also acts as a fibrin(ogen)olytic protease [13] suggest that Bi-VSP is used to facilitate the spread of bee venom throughout the bloodstream, as has been demonstrated for snake venom fibrin(ogen)olytic enzymes, which remove fibrinogen effectively and, thereby, reduce blood viscosity [23], [24]. Given the similarity in plasmin targeting with textilinin-1, an anti-bleeding agent [7][9], Bi-KTI is likely to be an antifibrinolytic agent that reduces bleeding at the sting site of victims.…”
Section: Resultsmentioning
confidence: 96%
“…Another serine protease of this family, named Bi-VSP, has a dual behavior, since in arthropods it triggers the phenoloxidase cascade inducing a lethal immune response, while in mammals it acts as a toxic thrombin-like and plasmin-like fibrinolytic protease (Choo et al, 2010). …”
Section: Bee Venommentioning
confidence: 99%
“…Bumblebee venom contains several toxic proteins and peptides, including bombolitin, phospholipase A 2 , serine proteases, and serine protease inhibitors (Xin et al, 2009;Choo et al, 2010aChoo et al, , b, 2012Qiu et al, 2011). Recent studies have been demonstrated that bumblebee venom serine proteases and serine protease inhibitors act as fibrin(ogen)olytic agents (Choo et al, 2010b;Qiu et al, 2011) and antifibrinolytic agents (Choo et al, 2012), respectively. Serine protease inhibitors are ubiquitous in numerous tissues and organisms, including animals, plants, and microbes.…”
Section: Introductionmentioning
confidence: 99%